SIKLUS UNDERUTILIZATION ANGKUTAN UMUM KONVENSIONAL KABUPATEN KEBUMEN: BASIS DIAGNOSTIK BAGI PERENCANAAN ANGKUTAN MASSAL - Wahyu Susilojati; Sabrina Handayani; Dessy Angga Afrianti; Panji Pasa Pratama (Berajah Journal, 2026)
Evaluations of public transportation performance in Indonesia generally assume a problem of excess demand, even though not all regions face this condition. This study examined the performance of 18 rural transportation routes in Kebumen Regency and found the opposite pattern: chronic underutilization, rather than overcrowding. Using a descriptive-quantitative approach with a case study design, data were collected through static surveys, dynamic (on-board) surveys, passenger interviews, and spatial analysis of route networks, and then compared Director General of Land Transportation Decree No. SK.687/AJ.206/DRJD/2002. The results show a service frequency of only 2–5 vehicles per hour, a headway of 23–68 minutes, and an average load factor of 7–29%—far below the 70% threshold on public transport service. This poor performance is not due to limited physical accessibility (59% of users live less than 100 meters from a service point), but rather to a structural preference for informal modes of transport (62% of users switched from motorcycle taxis or pedicabs). At the network level, service coverage is only 20.9% of the total area, with route overlap reaching 89%, compounded by a fleet age that far exceeds the roadworthiness threshold (14–29 years). These findings form a self-reinforcing cycle of declining performance involving low service reliability, user migration, and operators’ weak investment capacity. This study fills a gap in the literature that separates evaluations of conventional transit from post-implementation evaluations of BRT systems by positioning patterns of underutilization as a pre-planning diagnostic tool and a basis for decision-making in the planning of mass transit systems across various urban areas with diverse demographic characteristics, including both metropolitan areas and other developing regions.